Peningkatan Kapasitas SDM di Bidang Penguasaan Bahasa Inggris Desa Buwun Sejati Kabupaten Lombok Barat - Hasnia Minanda; Baiq Nikmatul; Mahmudah Budiatingsih; Siti Hamdiah Rojabi; Wahyu Hidayat; Alfin Asnawi Munsyir (Program Studi Pariwisata, Fakultas Ekonomi dan Bisnis,Universitas Mataram, 2023)
Desa Buwun Sejati is one of the tourist villages located in the Narmada District of West Lombok Regency, which boasts rich natural potential. Desa Buwun Sejati achieved the 2nd runner-up position in the category of Pilot Tourist Village in the 2022 Indonesian Tourism Village Awards (ADWI). Based on discussions with the Tourism Awareness Group (Pokdarwis) of Desa Wisata Buwun Sejati, one of their challenges is the low proficiency in the English language. Therefore, the Pokdarwis of Desa Buwun Sejati, through its leader, expressed the urgent need for English language training. They find it difficult to communicate and explain the attractions of tourism in Desa Buwun Sejati to international tourists due to their limited English proficiency. The objective of this initiative is to provide English language training specifically tailored for tourism, which will be attended by members of the Pokdarwis in Desa Buwun Sejati. Members participating in this tourism-focused English language training will be awarded certificates indicating their proficiency in the English language. This language proficiency will assist them in welcoming international tourists visiting Desa Buwun Sejati. It is hoped that through this initiative, it can support the development of tourism in Desa Buwun Sejati.